A Long Goodbye to Bismarck? The Politics of Welfare Reform in Continental Europe - Palier, Bruno (Changing Welfare States, 2010)
This book provides an extensive and comparative account of all welfare reforms that occurred during the last three decades in Continental European countries. It reveals unexpected important structural reforms, to be understood as the culmination of a long reform trajectory, analyzed in detail with the tools of comparative historical institutionalism. With these reforms, Bismarckian welfare systems have lost their encompassing capacities, have partially turned to employment-friendliness and weakened the strongest elements of their male breadwinner bias. "This volume is the definitive work on the politics of reform in Bismarckian welfare regimes. It is essential reading for any scholar interested in welfare reform - or indeed, in institutional and policy change more generally." (Kathleen Thelen, Massachusetts Institute of Technology ) "The contributors to the volume are all recognized experts on their field and provide strictly comparable analyses in their chapters, making this volume a gold mine for comparative welfare state scholars. Palier's volume is certain to be a benchmark study for the foreseeable future." (John D. Stephens, University of North Carolina, Chapel Hill) "This volume, representing the best available scholarship in comparative socio-economic research, provides important and highly policy-relevant insights. A must-read." (Fritz Scharpf, Max Planck Institute for the Studies of Societies) This title is available in the OAPEN Library - http://www.oapen.org.